Temperature-controlled liquid crystals alignment on solution-derived bismuth lanthanum tin oxide films prepared through brush process. Issue 15 (8th December 2022) - Kim, Dong Hyun; Lee, Dong Wook; Oh, Jin Young; Won, Jonghoon; Kim, Dai-Hyun; Liu, Yang; Seo, Dae-Shik
ABSTRACT: In this study, a bismuth – lanthanum–tin oxide film was fabricated via brush coating to obtain a process-efficient liquid crystal (LC) alignment layer. The brush-coating solution was prepared through a sol – gel process, applied onto an indium tin oxide glass, and cured at various temperatures. The shearing stress caused by the brush coating process formed a micro-/nanogroove structure, as confirmed via atomic force microscopy and line profile analyses. The chemical composition of the surface was analysed through X-ray photoelectron spectroscopy, and the optical transmittance of the film was measured. As regards the LC alignment, polarised optical microscopy observations, thermal stability tests, and pretilt angle measurements were performed, confirming a stable alignment; the grooves generated during the shearing and hardening phases were most clearly formed after curing at 180°C, which led to stable LC orientation. GRAPHICAL ABSTRACT: uf0001